2004
DOI: 10.1073/pnas.0306993101
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric hydrogenation of α,β-unsaturated phosphonates with Rh-BisP* and Rh-MiniPHOS catalysts: Scope and mechanism of the reaction

Abstract: Optically active 1,2-bis(alkylmethylphosphino)ethanes and bis(alkylmethylphosphino)methanes are unique diphosphine ligands combining the simple molecular structure and P-stereogenic asymmetric environment. This work shows that these ligands exhibit excellent enantioselectivity in rhodium-catalyzed asymmetric hydrogenation of ␣,␤-unsaturated phosphonic acid derivatives. The enantioselective hydrogenation mechanism elucidated by NMR study is also described. The ␣-hydroxy-and ␣-aminophosphonic acids have an extre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(33 citation statements)
references
References 44 publications
(68 reference statements)
1
29
0
Order By: Relevance
“…[69][70][71][72] Recently, Pizzano et al 73 reported the synthesis of enantiomerically pure (R)-GABOB P 7 via the highly enantioselective hydrogenation of enol ester phosphonate 84. Thus, the reaction of b-ketopropylphosphonate 83 with NaH followed by the addition of benzoyl chloride (BzCl) afforded the corresponding enol Z-84 as the only isomer isolable, which by catalytic hydrogenation in the presence of complex [Rh(cod) (85)]BF 4 , (cod = cycloocta-1,5-diene) gave the b-benzyloxyphosphonate (R)-86 in 87% yield and 99% ee.…”
Section: Enantioselective Hydrogenation Of B-enol Ester Phosphonatesmentioning
confidence: 99%
“…[69][70][71][72] Recently, Pizzano et al 73 reported the synthesis of enantiomerically pure (R)-GABOB P 7 via the highly enantioselective hydrogenation of enol ester phosphonate 84. Thus, the reaction of b-ketopropylphosphonate 83 with NaH followed by the addition of benzoyl chloride (BzCl) afforded the corresponding enol Z-84 as the only isomer isolable, which by catalytic hydrogenation in the presence of complex [Rh(cod) (85)]BF 4 , (cod = cycloocta-1,5-diene) gave the b-benzyloxyphosphonate (R)-86 in 87% yield and 99% ee.…”
Section: Enantioselective Hydrogenation Of B-enol Ester Phosphonatesmentioning
confidence: 99%
“…Rh complexes of BPE, DuPhos [172] , t Bu -BisP * , t Bu -MiniPhos [173] , and 13 [174] are also studied for the hydrogenation of enol phosphate (Fig. 7.21 ).…”
Section: Enol Estersmentioning
confidence: 99%
“…In 2004, Imamoto et al 151 described that the catalytic hydrogenation of dehydroaminophosphonate 248 in the presence of rhodium complex ( R,R )- t -BuBisP* 249 gave the ( R )-α-aminophosphonate 250 in 90% ee (Scheme 65). …”
Section: Stereoselective Synthesis Of α-Aminophosphonic Acids and mentioning
confidence: 99%